ANALISIS KELAYAKAN INVESTASI ALAT ROLL STREAPING PADA UKM MEKAR HANDCRAFT - Zaini, Ahmad; Riyadi, Slamet; Wati, Putu Eka Dewi Karunia (TEKNIKA, 2023)
UKM "Mekar Handcraft" is one of the small and medium enterprises that produces woven bags. In the initial process of producing woven bags, the manual tool used for cutting the strapping rope is a wooden block with nails. Later on, the production of woven bags switched to using a tool called a roll strapping gun. However, the roll strapping gun encountered some challenges, such as the inability to use certain raw materials with the spinning tool, leading to manual use by workers. Additionally, the position of the raw material roll was too close to the roll, causing frequent breakage of the strapping rope. The introduction of the new strapping tool is expected to accelerate the production process in the SME. Therefore, a feasibility study analysis is necessary to determine the viability of investing in the roll strapping tool. Based on this research, a positive Net Present Value (NPV) calculation of (Rp.212,450) was obtained, indicating that the investment is feasible (NPV > 0). The Internal Rate of Return (IRR) was calculated to be 11.29%, which is higher than the interest rate (MAAR) of 9% used, indicating the feasibility of the investment. The Payback Period calculation resulted in 10.78 months or 324 days, and considering the economic lifespan of the roll strapping machine as 10 years, the investment in the roll strapping tool is deemed feasible. Furthermore, the Profitability Index (PI) calculation yielded a value of 1.11, which is greater than 1, confirming the feasibility of the machine purchase investment.